EFISENSI PENGGANTIAN PIPA PENSTOCK PLTA SIMAN DENGAN METODE WELDED LAP JOINT - Ranti Hidayawanti (FORUM MEKANIKA, 2017)
Penstock of PLTA Siman had experienced several improvements such as leak repair with welding, rivet and coating replacement. Therefore, an assessment of PLTA Siman displacement is required. PLTA Siman displacement work must be reviewed comprehensively and up-to-date on operations, environmental, equipment, and risks of worker involved in replacing the penstock work. PLTA Siman is located in the last position of cascade 3 PLTA Selorejo - Mendalan - Siman with primary energy taken from Selorejo dam. From the Selorejo dam, in sequence water is used as primary energy in PLTA Selorejo, then PLTA Mendalan, and ended at PLTA Siman. The output of the PLTA Mendalan is accommodated first in the PLTA Siman pond. From the pond, water is flowed through a closed channel to the main valve, which has a primary function for isolating (via the main valve equipment) and for removing excess pressure (via surge tank equipment). From this main valve, water is flowed through a penstock before being split for 3 units of PLTA SIman generator turbine PLTA. The replacement planning of penstock PLTA Siman is done so that the implementation during the replacement work has covered all the risk that might arise so that mistakes of replacement work can be minimized. The type of joint is very influential on the result of this penstock replacement. From several type of penstock joint, Welded Lap Joint and Welded Butt Joint are the most effective and efficient for welding work of this penstock replacement. while from the topographical of the work area as well as proper material selection, it is helpful to anticipate the completion of possible friction due to contraction of temperature changes